2022
DOI: 10.3390/foods11121696
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microecology of Mice Exposed to TiO2 Nanoparticles and Bisphenol A

Abstract: Exposure to titanium dioxide nanoparticles (TiO2 NPs) and bisphenol A (BPA) is ubiquitous, especially through dietary and other environmental pathways. In the present study, adult C57BL/6J mice were exposed to TiO2 NPs (100 mg/kg), BPA (0, 5, and 50 mg/kg), or their binary mixtures for 13 weeks. The 16S rDNA amplification sequence analysis revealed that co-exposure to TiO2 NPs and BPA altered the intestinal microbiota; however, this alteration was mainly caused by TiO2 NPs. Faecal metabolomics analysis reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…We found that B. coagulans could also ameliorate the reduction in intestinal microbial species resulting from exposure to TiO 2 NPs ( Table 2 ) and modulate the composition of gut microbiota ( Figure 5 and Figure 6 ). Previously, our research group found that the relative abundance of Lactobacillus in the guts of mice exposed to TiO 2 NPs increased in a dose-dependent manner [ 10 ], which corresponded to other research, and the researchers suggested that the increase in Lactobacillus may be a key factor in the influence of TiO 2 NPs on gut microbiota [ 35 ]. Lactobacillus_gasseri was able to cause gangrene, leading to increased ROS production [ 52 ].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We found that B. coagulans could also ameliorate the reduction in intestinal microbial species resulting from exposure to TiO 2 NPs ( Table 2 ) and modulate the composition of gut microbiota ( Figure 5 and Figure 6 ). Previously, our research group found that the relative abundance of Lactobacillus in the guts of mice exposed to TiO 2 NPs increased in a dose-dependent manner [ 10 ], which corresponded to other research, and the researchers suggested that the increase in Lactobacillus may be a key factor in the influence of TiO 2 NPs on gut microbiota [ 35 ]. Lactobacillus_gasseri was able to cause gangrene, leading to increased ROS production [ 52 ].…”
Section: Discussionsupporting
confidence: 76%
“…Numerous studies have documented intestinal damage, as, after ingestion, TiO 2 NPs stay for extended periods in the intestinal tract and interact with intestinal microorganisms and intestinal epithelial cells [ 7 , 8 , 9 , 10 ]. Gut microbiota is an ecosystem with complex interactions, which plays a vital role in human health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…105,106 Yang et al determined the impact of TiO 2 NPs on the composition and metabolic parameters of gut microbiota in diabetic mice, illustrating enhanced glucose metabolism and insulin sensitivity. 107…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…Hippocrates, the father of Western medicine, once said, ‘All diseases begin in the gut’. Modern medical research has further verified that intestinal health plays a vital role in human health [ [ 6 , 7 ]]. As a microbial community resident in the body's intestines, intestinal flora plays a decisive role in intestinal health and participates in regulating various physiological functions of the human body.…”
Section: Introductionmentioning
confidence: 99%